2012
DOI: 10.1152/ajpheart.00004.2012
|View full text |Cite
|
Sign up to set email alerts
|

Unprovoked atrial tachyarrhythmias in aging spontaneously hypertensive rats: the role of the autonomic nervous system

Alina Scridon,
Clément Gallet,
Moussa M. Arisha
et al.

Abstract: Experimental models of unprovoked atrial tachyarrhythmias (AT) in conscious, ambulatory animals are lacking. We hypothesized that the aging, spontaneously hypertensive rat (SHR) may provide such a model. Baseline ECG recordings were acquired with radiotelemetry in eight young (14-wk-old) and eight aging (55-wk-old) SHRs and in two groups of four age-matched Wistar-Kyoto (WKY) rats. Quantification of AT and heart rate variability (HRV) analysis were performed based on 24-h ECG recordings in unrestrained rats. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Given that during pacing waves are difficult, if not impossible, to recognize, AF duration is usually measured from the end of burst pacing to the first P wave detected after the irregular supraventricular rhythm. In accordance with previous studies (8), AF was defined in this study as rapid, irregular, supraventricular rhythm, with no visible P waves and irregular R-R intervals, lasting at least three beats. In other studies, a duration of at least 2 s was required to define AF (10).…”
Section: Atrial Fibrillation Inducibilitymentioning
confidence: 59%
See 3 more Smart Citations
“…Given that during pacing waves are difficult, if not impossible, to recognize, AF duration is usually measured from the end of burst pacing to the first P wave detected after the irregular supraventricular rhythm. In accordance with previous studies (8), AF was defined in this study as rapid, irregular, supraventricular rhythm, with no visible P waves and irregular R-R intervals, lasting at least three beats. In other studies, a duration of at least 2 s was required to define AF (10).…”
Section: Atrial Fibrillation Inducibilitymentioning
confidence: 59%
“…Moreover, in the presence of substrate-modifying factors such as aging and hypertension, rat hearts develop spontaneous AF (8). Although it replicates well the human condition, AF occurrence in this latter model requires long-term (>12 months) follow-up (8).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Contrarily, based on the panel of studied genes, it appears that the ventricular myocardium is much less 'sensitive' to molecular aging, explaining the lower propensity to ventricular than atrial arrhythmias of the elderly. However, despite the pro-arrhythmic atrial molecular profile, we previously demonstrated using continuous electrocardiographic recordings that aging WKY rats do not develop significant atrial arrhythmic events, contrary to aging spontaneously hypertensive rats, which displayed high atrial arrhythmogenicity (28). Taken together, these observations suggest that atrial molecular aging is not a sufficient condition but more likely a facilitator of atrial arrhythmogenicity, and that the presence of other factors, such as arterial hypertension, is needed in order to initiate the arrhythmias.…”
Section: Transcripts With Putative Roles In Aging-related Cardiac Arrmentioning
confidence: 86%